2010
DOI: 10.1117/1.3495720
|View full text |Cite
|
Sign up to set email alerts
|

System for interstitial photodynamic therapy with online dosimetry: first clinical experiences of prostate cancer

Abstract: Abstract. The first results from a clinical study for Temoporfinmediated photodynamic therapy ͑PDT͒ of low-grade ͑T1c͒ primary prostate cancer using online dosimetry are presented. Dosimetric feedback in real time was applied, for the first time to our knowledge, in interstitial photodynamic therapy. The dosimetry software IDOSE provided dose plans, including optical fiber positions and light doses based on 3-D tissue models generated from ultrasound images. Tissue optical property measurements were obtained u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 26 publications
2
79
0
2
Order By: Relevance
“…Swartling et al researched the interstitial PDT with online feedback to deliver a tailored light fluence dose, exceeding a predefined threshold dose, to the whole prostate gland and adapt the dose plan in cases where the optical attenuation changes during the therapy. 30 They have reported that the optical properties of the gland tissue did not markedly vary during the treatment with Foscan R in clinical study. But, Thompson et al reported that light transmission decreased in nodular basal cell carcinomas during 5-amino levulinic acid mediated PDT.…”
Section: Penetration Depth Of Light Within Tumor Tissues During Photomentioning
confidence: 99%
“…Swartling et al researched the interstitial PDT with online feedback to deliver a tailored light fluence dose, exceeding a predefined threshold dose, to the whole prostate gland and adapt the dose plan in cases where the optical attenuation changes during the therapy. 30 They have reported that the optical properties of the gland tissue did not markedly vary during the treatment with Foscan R in clinical study. But, Thompson et al reported that light transmission decreased in nodular basal cell carcinomas during 5-amino levulinic acid mediated PDT.…”
Section: Penetration Depth Of Light Within Tumor Tissues During Photomentioning
confidence: 99%
“…In the practice of interstitial PDT delivery, however, patient optical properties vary widely [33,34]. Development of treatment plans which are robust to a range of optical properties, as well as techniques for in-vivo detection and compensation for such variability (building on prior efforts in the prostate [4,25]), would be important contributions to PDT practice. The first part involving assessment of variability is enabled in a straightforward way by the present work, requiring only simulation of clinicallyderived meshes over a range of properties with analysis of the results.…”
Section: Optical Property Variabilitymentioning
confidence: 99%
“…Researchers at Lund University and SpectraCure AB [25] have run clinical trials for prostate cancer using the SpectraCure IDOSE platform, which uses multiple treatment fibers and realtime monitoring. Their planning system uses a diffusion-based solver to calculate light fluence, aiming to deliver a minimum threshold dose to the entire prostate gland while minimizing exposure to nearby organs [26].…”
Section: Pdt Treatment Geometry Evaluationmentioning
confidence: 99%
“…10 Techniques involving separate spectroscopy instruments require the insertion of additional needles into the target volume, increasing the risk and complexity of the procedure. Investigators at Lund University have replaced the treatment diffusers with flat-cleaved fibers that are also used for optical property determination, 11 reducing the complexity. However, when flat-cleaved fibers are used for treatment, we have previously shown that treatment time and the number of fibers required to adequately cover the tumor volume are both increased.…”
Section: Introductionmentioning
confidence: 99%